Komitmen Lingkungan dan Budaya CSR Kreatif Multitema Batik Alam Malon PT Indonesia Power Semarang Power Generation Unit - Agus Naryoso (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2020)
Corporate Social Responsibility (CSR) activities are performed not only for legal compliance or carrying out the mandate of the law Corporate Social Responsibility (CSR) is not only a recommendation from the government to business people but also an obligation that must be implemented by companies both private and government business. Law No. 40/2007 mandates that all companies allocate funds from business proceeds for social activities as a form of commitment to the surrounding environment. PT Indonesia Power Semarang Power Generation Unit consistently responds and carries out this obligation. This obligation is done not to avoid government sanctions and reprimands but as an effort to balance and harmonize the business interests of the company with a commitment to the environment, economic independence, and efforts to preserve culture. This paper uses a descriptive type of research with a communication audit analysis approach. Data collection was carried out by interviewing various relevant sources from internal circles and also beneficiaries of Multi-theme CSR activities in Batik Alam Malon, Gunungpati Subdistrict, Semarang City.